Կարծրատիպերի ձևավորումը և ազդեցությունը ավագ նախադպրոցականի կոգնիցիայի դրսևորման գործընթացում - Գայանե Մարգարյան (ՀՀ ԳԱԱ հրատ.)
В данной статье представлены факторы способствующие формированию укоренившихся стереотипов, которые имеют деструктивное влияние на когнитивные проявления у детей старшего дошкольного возраста. This article presents factors contributing to the formation of entrenched stereotypes that have destructive effects on cognitive manifestations on children of older preschool age are presented.
Keywords: Psychology; Education; Primary Education